Revascularization of chronic total occlusion coronary artery and cardiac regeneration - Ruoxi Liao; Zhihong Li; Qiancheng Wang; Hairuo Lin; Huijun Sun (Frontiers in Cardiovascular Medicine, 2022)
Coronary chronic total occlusion (CTO) contributes to the progression of heart failure in patients with ischemic cardiomyopathy. Randomized controlled trials demonstrated that percutaneous coronary intervention (PCI) for CTO significantly improves angina symptoms and quality of life but fails to reduce clinical events compared with optimal medical therapy. Even so, intervening physicians strongly support CTO-PCI. Cardiac regeneration therapy after CTO-PCI should be a promising approach to improving the prognosis of ischemic cardiomyopathy. However, the relationship between CTO revascularization and cardiac regeneration has rarely been studied, and experimental studies on cardiac regeneration usually employ rodent models with permanent ligation of the coronary artery rather than reopening of the occlusive artery. Limited early-stage clinical trials demonstrated that cell therapy for cardiac regeneration in ischemic cardiomyopathy reduces scar size, reverses cardiac remodeling, and promotes angiogenesis. This review focuses on the status quo of CTO-PCI in ischemic cardiomyopathy and the clinical prospect of cardiac regeneration in this setting.